Enrichment of Fermented Lemna in Commercial Feed and Its Effect in Improving the Perfomance of Common Carp (Cyprinus carpio) Infected by Aeromonas hydrophila Bacteria - Haetami, Kiki; Syifa, Jeni Ghina; Iskandar; Grandiossa, Roffi (Department of Aquaculture, 2025)
Common carp (Cyprinus carpio) is one of the main commodities of aquaculture production in Indonesia, especially West Java. The processing of Lemna through the fermentation process is one of the efforts to improve quality alternative feed ingredients that function as prebiotics. The growth of common carp infected with the disease tends to be disturbed, so that the growth rate is inhibited. This study aims to determine the effect of the level of addition of Lemna minor flour from the enrichment of BIOMS probiotics in feed on the growth of common carp infected with Aeromonas hydrophila bacteria. The method used in this study was a Complete Randomized Design (CRD) experiment with 5 treatments and 4 replicates. The calculation of the measurement of test fish samples was carried out 4 times for 30 days. The data was analyzed using variety analysis (ANOVA). The conclusion of this study is that the addition of Lemna flour enriched with fermented BIOMS probiotics in feed provides an increase in SGR (Specific Growth Rate) value, a decrease in FCR (Feed Conversion Rate) value, and an increase in FE (Feed Efficiency) value of fish that is better than fish fed commercial feed (control +) and lemna without enrichment (control -). Feeding with the addition of fermented Lemna flour can increase the growth of common carp, such as SGR (0.34 ± 0.0599) and EP (68%), as well as reduce the FCR value (1.51 ± 0.3161).